2018
DOI: 10.31768/2312-8852.2018.40(2):136-139
|View full text |Cite
|
Sign up to set email alerts
|

The State of Bone Metabolism in Lung Cancer Patients

Abstract: In recent years, we have discussed the correlation of malignant tumor process with the development of osteoporosis, which can be exacerbated by ongoing chemotherapy and radiation therapy. The aim of the work was to assess the status of bone metabolism in 32 untreated patients with lung cancer without metastasis. Materials and Methods: Patients underwent dual-energy X-ray osteodensitometry of proximal part of femoral bone. Osteopontin (OP), osteocalcin (OC) and alkaline phosphatase (AP) parameters were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Secondly, the guideline addresses the negative effects of anti-cancer therapies (such as chemotherapy and radiation) on reproductive hormones that are crucial for the maintenance of bone remodeling. The study of Dumanskiy et al on bone metabolism in lung cancer patients has shown that they had significantly higher serum levels of some macro-and microelements (such as cobalt, lithium, and phosphorus) compared with healthy controls (21). Conversely, calcium and magnesium were significantly lower.…”
Section: Discussionmentioning
confidence: 96%
“…Secondly, the guideline addresses the negative effects of anti-cancer therapies (such as chemotherapy and radiation) on reproductive hormones that are crucial for the maintenance of bone remodeling. The study of Dumanskiy et al on bone metabolism in lung cancer patients has shown that they had significantly higher serum levels of some macro-and microelements (such as cobalt, lithium, and phosphorus) compared with healthy controls (21). Conversely, calcium and magnesium were significantly lower.…”
Section: Discussionmentioning
confidence: 96%
“…17 Similarly, cervical cancer patients were found to present lower bone mineral density in the absence of bone metastases, 18 whereas 40% of patients affected by non-small lung cancer without tumor dissemination to bone were shown to present with osteoporosis and osteopenia. 19 Several preclinical models for the study of cancer support the idea that bone alterations can occur in the absence of bone metastases. We showed that mice bearing the ES-2 ovarian cancer or the MC-38 colorectal cancer present with severe bone loss along with the development of skeletal muscle atrophy and weakness.…”
Section: Features Of Cachexiamentioning
confidence: 99%
“…Skeletal metastatic disease is also a common cause of deregulated bone metabolism due to pathological cross-talk between tumor cells and the bone milieu [ 29 ]. Interestingly, osteopenia and osteoporosis have also been observed in therapy-naïve patients without evidence of skeletal involvement [ 8 , 9 ], thus suggesting that additional factors other than bone metastases and treatments may affect bone turnover in cancer patients. At first diagnosis as many as 42% of oncological patients present signs of cachexia [ 30 ], a multiorgan syndrome characterized by weight loss, wasting of muscle mass and systemic inflammation; all of which are frequently associated with bone loss [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer patients, bone damage results most frequently from skeletal metastatic disease, but is also a complication of anti-tumoral agents, hormone-targeted strategies in particular [ 7 ]. Importantly, osteopenia has also been documented in therapy-naïve patients without evidence of skeletal involvement [ 8 , 9 ]. Indeed, systemic inflammation, muscle wasting, and weight loss may contribute to bone mineral loss, as observed in patients with chronic heart failure or arthritis [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%